Uncommon congenital swellings around external ear in adults - Desai, Nidhi; Vare, Reena; Vare, Anil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Congenital cyst around external ear appearing in adulthood is rare condition. Such lesions arising around the external auditory canal that requires surgical excision are uncommon and their clinical and surgical management is often difficult because these anomalies have variable relationship with facial nerve. In this study, we investigated characteristics of congenital cysts of the external ear by analyzing their clinical and histo-pathological features. Here we described 3 unique cases with localization of an epithelial cyst, type 1 branchial cleft cyst and epidermal inclusion cyst in adults which are uncommon, congenital and rare.